2000
DOI: 10.1093/hmg/9.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest enhances the in vitro cellular toxicity of the truncated Machado-Joseph disease gene product with an expanded polyglutamine stretch

Abstract: Machado-Joseph disease (MJD) is an inherited neurodegenerative disorder caused by the expansion of the polyglutamine stretch in the MJD gene-encoded protein, ataxin-3. Using a series of deletion constructs expressing ataxin-3 fragments with expanded polyglutamine stretches, we observed aggregate formation and cell death in cultured BHK-21 cells. The cytotoxic effect of N-terminal-truncated ataxin-3 with the expanded polyglutamine tract was enhanced under serum starvation culture, in which cells were arrested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 39 publications
1
38
1
1
Order By: Relevance
“…Previous reports indicated that a C-terminal portion of mutant ataxin-3 mjd1a containing the polyglutamine expansion was cytotoxic, whereas the full-length form was not (Ikeda et al, 1996;Paulson et al, 1997b;Warrick et al, 1998;Yoshizawa et al, 2000). Thus, we determined whether the putative-cleavage fragment that we detected in brain corresponded to a C-terminal portion of mutant ataxin-3 mjd1a containing the polyglutamine expansion.…”
Section: Composition Of the Mutant Ataxin-3 Putative-cleavage Fragmentmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous reports indicated that a C-terminal portion of mutant ataxin-3 mjd1a containing the polyglutamine expansion was cytotoxic, whereas the full-length form was not (Ikeda et al, 1996;Paulson et al, 1997b;Warrick et al, 1998;Yoshizawa et al, 2000). Thus, we determined whether the putative-cleavage fragment that we detected in brain corresponded to a C-terminal portion of mutant ataxin-3 mjd1a containing the polyglutamine expansion.…”
Section: Composition Of the Mutant Ataxin-3 Putative-cleavage Fragmentmentioning
confidence: 85%
“…Previous work using transgenic animals and transfected cells demonstrated that neuronal toxicity is caused by mutant ataxin-3 mjd1a truncations, to include the polyglutamine expansion, but not the full-length protein (Ikeda et al, 1996;Paulson et al, 1997b;Warrick et al, 1998;Yoshizawa et al, 2000;Hara et al, 2001). Thus, it was proposed that a mutant ataxin-3 mjd1a toxic cleavage fragment is released in affected but not spared neurons (Ikeda et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Because the expanded form of ataxin-3 is more toxic for nondividing or postmitotic cells, it may be significant that neurons are postmitotic (51). It is possible that nonneuronal cells have developed mechanisms to cope with the failure of mutant ataxin-3 to maintain efficient degradation of proteolytic substrates.…”
Section: Discussionmentioning
confidence: 99%
“…To ablate these neurons, we used a toxin-mediated genetic cell ablation strategy using a truncated Machado-Joseph disease gene product (ataxin-3) under the control of an MCH promoter. The ataxin-3 transgene has been used to induce apoptosis in cells in vitro and for the ablation of orexin neurons in vivo (Yoshizawa et al, 2000;Hara et al, 2001). As described below, the ablation of MCH neurons results in significant weight loss developing later in life.…”
Section: Introductionmentioning
confidence: 99%